Pengaruh Kualitas Pendidikan, Biaya Pendidikan dan Lokasi Terhadap Kepuasan Siswa pada SMK Swasta PAB 8 Sampali - Astari, Nurizka; Tanjung, Yahya (Education Achievement: Journal of Science and Research, 2025)
thesis entitled "The Influence of Education Quality, Education Costs and Location on Student Satisfaction at PAB 8 Sampali Private Vocational School" is the result of quantitative research which aims to answer questions about the influence of education quality, education costs and location on student satisfaction at PAB 8 Sampali Private Vocational School. The research methodology used is quantitative research using a sampling technique using simple probability sampling with a total of 85 respondents. The data collection technique uses a questionnaire processed using SPSS version 25. Data analysis uses multiple linear regression. Based on partial research results, the variable quality of education has a positive and significant effect on student satisfaction with a calculated t value of 3,638 > t table 1,664 and a significant value of 0.000 < 0.05, education costs has no significant effect on student satisfaction with a calculated t value of 0.652 < t table 1,664 and a significant value of 0.516 < 0.05 and location has a positive and significant effect on student satisfaction with a calculated t value of 2,599 > t table 1,664 and a significant value of 0.011 < 0.05 at PAB 8 Sampali Private Vocational School. And simultaneously shows that the variables of education quality, education costs and location have a significant and positive effect on student satisfaction with a calculated f value of 62,852 > f table 2.72 and a significant value of 0.000 < 0.05.